2012
DOI: 10.1108/s2043-9059(2012)0000004017
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Stakeholder Relationships Using ‘Corporate Social Responsibility’ as a Response Strategy to Cases of Corporate Irresponsibility: The Case of the 2010 BP Spill in the Gulf of Mexico

Abstract: Purpose À When organisations behave irresponsibly, a question remains: Can they use a messaging strategy based in the organisation's commitment social responsibility to effectively respond to the crisis? The purpose of this chapter is to analyse stakeholder attitudes and their antecedents in such a case. Because of its scope, magnitude and use of a response strategy based on messages of social responsibility, the 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In many cases, stakeholder evaluations of an organization's intentions towards a crisis come down to their belief that the organization is genuinely committed to improving the situation . Diers (2012) model that has been studied the most in crisis communication. Often treated as an outcome of a crisis, these judgments have been assessed across multiple fields of study from communication and marketing to industry-specific studies in such different areas like health care and tourism.…”
Section: Stakeholder Evaluations Of An Organization's Role In a Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, stakeholder evaluations of an organization's intentions towards a crisis come down to their belief that the organization is genuinely committed to improving the situation . Diers (2012) model that has been studied the most in crisis communication. Often treated as an outcome of a crisis, these judgments have been assessed across multiple fields of study from communication and marketing to industry-specific studies in such different areas like health care and tourism.…”
Section: Stakeholder Evaluations Of An Organization's Role In a Crisismentioning
confidence: 99%
“…If researchers and practitioners want to understand this relationship, they should be directly analyzing factors like changes to an organization's reputation with an immense body of study ranging from the evolution of image restoration in the 1990's (Benoit, 1995) to studies of reputational crises themselves to experimental evaluations of factors evaluating the impact of crises on reputation (Kim & Lee, 2015). However, Diers (2012) found that other factors like stakeholders' perceived knowledge of the organization not only changed under different crisis circumstances but also influenced their overall perception of the crisis. For example, she found that if a crisis made stakeholders feel like they had less knowledge about an organization, the stakeholders were more likely to evaluate the organization negatively.…”
Section: Stakeholder Evaluations Of An Organization's Role In a Crisismentioning
confidence: 99%
“…In her analysis of public evaluations of BP 1 year after the 2010 Gulf spill, Diers () proposed a relational model of corporate image assessment, arguing that we can better assess the degree to which an organization's efforts to communicate corporate social responsibility have been successful. In the case of BP, Diers () found that while its message strategy had limited positive effects on stakeholder assessments of BP as a ‘socially responsible’ organization, the company did seem to ‘open the lines of communication between stakeholders and the company’ (p. 178). Additionally, instead of being callous as Bauman () suggested, previous analysis of BP's crisis response strategies (see Diers‐Lawson & Donohue, ) found that BP's response to the crisis centred on messages of corporate social responsibility with a particularly a strong emphasis on communicating caring about the people and environment affected by the spill.…”
Section: A Relationship‐based Ethical Apology Frameworkmentioning
confidence: 99%
“…In her analysis of public evaluations of BP 1 year after the 2010 Gulf spill, Diers () proposed a relational model of corporate image assessment, arguing that we can better assess the degree to which an organization's efforts to communicate corporate social responsibility have been successful. In the case of BP, Diers () found that while its message strategy had limited positive effects on stakeholder assessments of BP as a ‘socially responsible’ organization, the company did seem to ‘open the lines of communication between stakeholders and the company’ (p. 178).…”
Section: A Relationship‐based Ethical Apology Frameworkmentioning
confidence: 99%
See 1 more Smart Citation